2020
DOI: 10.1021/acsanm.0c02713
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanoparticle–Graphene Composite-Based Transparent Surface Coating with Antiviral Activity against Influenza Virus

Abstract: Respiratory infections by RNA viruses are one of the major burdens on global health and economy. Viruses like influenza or coronaviruses can be transmitted through respiratory droplets or contaminated surfaces. An effective antiviral coating can decrease the viability of the virus particles in our surroundings significantly, hence reducing their transmission rate. Here, we have screened a series of nanoparticles and their composites for antiviral activity using a nanoluciferase-based highly sensitive influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…In the same vein, they assigned the H1N1 inhibitory effects to the denaturation of the viral HA protein interfering with host cell viral recognition. More recently, Das Jana and colleagues [ 25 ] showed the inhibitory effects of copper oxide (Cu 2 O) NPs in a composite with graphene sheets on influenza A virus after 30 min of contact. They ascribed the antiviral effects of Cu 2 O NPs to their interference with the structure and the function of viral HA, disrupting the viral structural integrity to enter host cells, and consequently preventing viral replication and infection.…”
Section: Resultsmentioning
confidence: 99%
“…In the same vein, they assigned the H1N1 inhibitory effects to the denaturation of the viral HA protein interfering with host cell viral recognition. More recently, Das Jana and colleagues [ 25 ] showed the inhibitory effects of copper oxide (Cu 2 O) NPs in a composite with graphene sheets on influenza A virus after 30 min of contact. They ascribed the antiviral effects of Cu 2 O NPs to their interference with the structure and the function of viral HA, disrupting the viral structural integrity to enter host cells, and consequently preventing viral replication and infection.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, a powerful and highly transparent antiviral coating for influenza or coronaviruses was prepared using copper oxide-embedded graphene as an antiviral agent and poly(vinyl alcohol). 39 This prepared coating can be used for a wide range of surfaces to reduce the transmission of respiratory viral infections. Structural investigation demonstrated the even dispersion of the CuO and Cu 2 O nanoparticles on 2D graphene sheets.…”
Section: The Role Of Copper and Copper Oxide Nanoparticles During The Covid-19 Crisismentioning
confidence: 99%
“…This figure has been reproduced from ref. 39 with permission from the American Chemical Society, copyright 2020. Fig.…”
Section: The Role Of Iron-based Nanoparticles During the Covid-19 Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, nanoparticles have raised great interest within the medical field due to their antiviral and antimicrobial properties, which make them an excellent focus of attention for conducting research to help combat infectious diseases, as they have shown great potential to solve different challenges [1,6,7]. There are a wide variety of synthesis methods or routes to obtain nanoparticles, known as chemical reduction, sol-gel, chemical vapor deposition (CVD), biochemical synthesis, green chemical synthesis, and sputtering synthesis, among others [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%